Modelling Landscape Changes and Detecting Land Cover Types by Means of Remote Sensing Data and ILWIS GIS - Lemenkova Polina (Zenodo, 2015)
Abstract. The emphasis of this article is placed on the technical application of the remote sensing tools and methods for studies of vegetation coverage in northern ecosystems. The study area is located in Yamal peninsula, the Russian Federation. Landsat imagery covering study area in 1988, 2001 and 2011 has been analyzed using ILWIS GIS. The image processing was performed using semi-automated method of image interpretation. The remote sensing data classification from ILWIS menu enabled to map vegetation coverage over research area, which helped to identify land cover types and distribution in Yamal. Results show that Landsat TM imagery with 30 m mesh spacing is useful for landscape mapping and the interpretation of the vegetation cover types. P. Lemenkova. "Modelling Landscape Changes and Detecting Land Cover Types by Means of Remote Sensing Data and ILWIS GIS". In: Bulletin of the Ufa State Petroleum Technological University 1.2 (2015): Information Technologies. Problems and Solutions. Ed. by F. U. Enikeev, pp. 265–271. issn: 2500-2996. url: https://elibrary.ru/item.asp?id=28416940.